Lumbar Spine Distraction Exercise—Surprisingly Innovation in Conservative Treatment of Degenerative Lumbar Spine Disorder. (May 2014) - Pandya, M.
Introduction: It is not possible to prevent the progression of degenerative disc disease of lumbar spine. Conservative treatment offered today help minimize the load coming on lumbar intervertebral disc (IVD). It has no useful effect in improving the important pathological change of degenerative lumbar disc disease that is impaired nutrition of IVD. Healthy IVD contracts during mechanical loading and expands on unloading. Nutrition of the IVD is possible only in expanded disc. Considering this pathophysiology of IVD, an exercise named lumbar spine distraction exercise was developed to distract intervertebral space with a view to make conservative treatment truly "effective" in degenerative lumbar disc disease. Materials and Methods: A study was conducted to see the effect of this exercise in 100 patients presented on outdoor from June 2008 to August 2009 with low backache with sciatica of any long duration. Patients with significant motor deficit or with possibility of psychiatric component were excluded. Magnetic resonance imaging (MRI) was done before treatment. Patients having functionally disabling low back pain were put on rest for a brief period of a day or 2 before the distraction exercise was started. Back care was taught to all patients. Patients were followed up first time at 1 week and then every 3 to 4 weeks. In random 20 patients out of 80 patients who were responding to the treatment and who had significant advanced MRI changes in pretreatment MRI, repeat MRI was done at 4 weeks, 8 weeks, and 6 months. Results: More than 80% (80/100) patients had significant subjective pain relief and had maintained satisfactorily improved functional capacity on average follow-up of 9 months. Objective findings on follow-up MRI such as widening of canal, increased interspinous distance, decompression of nerve root, increased whiteness of IVD, regression of Schmorl nodule, and correction of angles between vertebrae were seen in all patients followed up on MRI. Conclusion: Lumbar spine distraction exercise is a very promising exercise for low backache with sciatica. Subjective improvement (in few days) is much faster than MRI changes (few weeks). It could reduce number of surgery on lower back for degenerative lumbar spine disease and could also help those operated for neuromeningeal compression in preventing recurrence. Although number of patients in whom this exercise was used effectively as treatment is 100, small number of them (20) were followed up objectively with MRI at regular interval because of financial constraint. Disclosure of Interest None declared References McCulloh J, Transfeldt E. McNab's Backache. 3rd ed. Baltimore: Williams and Wilkins; 1997:75-83, 393–413 Patel RK, Slipman CW. Lumbar degenerative disk disease. Available at: http://emedicine.medscape.com/article/309767-diagnosis. Accessed August 28, 2009 Anderson G, Singh K, Kahill P, Lee M, Tannoury C, Zmurko M. In: Fischgrund J, ed. Orthopedic Knowledge Update [OKU 9]. Chicago: American Academy of Orthopedic Surgeons; 2008:531-540, 551–564 Pandya M. Degenerative Lumbar Spine Disorder and Its Conservative Treatment. 1st ed. New Delhi, India: Jaypee Brothers Publication; 2011 Waddell G, McCulloch JA, Kummel E, Venner RM. Nonorganic physical signs in low-back pain. Spine 1980;5(2):117–125 Williams KD, Park AL. Lower back pain and disorders of intervertebral discs. In: Canale ST, ed. Campbell's Operative Orthopaedics. Vol. 2. 10th ed. Philadelphia, PA: Mosby Elsevier; 2003:1955–2002 Magee DJ. Orthopedic Physical Assessment. 5th ed. Philadelphia: Elsevier Saunders; 2008:515–621 Netter FH. Atlas of Human Anatomy. 4th ed. Philadelphia: Elsevier Saunders; 2006:263 Richards JC, Majumdar S, Lindsey DP, Beaupré GS, Yerby SA. The treatment mechanism of an interspinous process implant for lumbar neurogenic intermittent claudication. Spine 2005;30(7):744–749